Effect of N,C-ITO on Composite N,C-Ti/N,C-ITO/ITO Electrode Used for Photoelectrochemical Degradation of Aqueous Pollutant with Simultaneous Hydrogen Production - Kee-Rong Wu; Chung-Hsuang Hung; Chung-Wei Yeh; Chien-Chung Wang; Jiing-Kae Wu (International Journal of Photoenergy)
This study reports the effect of N,C-ITO (indium tin oxide) layer on composite N,C-TiO2/N,C-ITO/ITO (Ti/TO) electrode used for efficient photoelectrocatalytic (PEC) degradation of aqueous pollutant with simultaneous hydrogen production. The structural properties of the composite Ti/TO electrode that determined by X-ray diffraction and Raman scattering, show primarily the crystallized anatase TiO2 phase and distinct diffraction patterns of polycrystalline In2O3 phase. Under solar light illumination, the composite Ti/TO electrode yields simultaneously a hydrogen production rate of 12.0 μmol cm−2 h−1 and degradation rate constant of  cm−2 h−1 in organic pollutant. It implies that the overlaid N,C-TiO2 layer enhances not only the photocurrent response of the composite Ti/TO electrode at entire applied potentials, but also the flat band potential; a shift of about 0.1 V toward cathode, which is desperately beneficial in the PEC process. In light of the X-ray photoelectron spectroscopy findings, these results are attributable partly to the synergetic effect of N,C-codoping into the TiO2 and ITO lattices on their band gap narrowing and photosensitizing as well. Thus, the Ti/TO electrode can potentially serve an efficient PEC electrode for simultaneous pollutant degradation and hydrogen production.